Infeksi Ganda Begomovirus dan Crinivirus pada Tanaman Tomat di Kabupaten Magelang, Jawa Tengah - Fitri Kusumaningrum; Sedyo Hartono; Sri Sulandari; Susamto Somowiyarjo (Jurnal Perlindungan Tanaman Indonesia, 2015)
Since 2006, a yellowing disease has been observed in tomato (Lycopersicon esculentum) fields in Central Java, Indonesia. Epidemics of the diseases were mainly associated with populations of the whitefly Trialeurodes vaporariorum and Bemisia tabaci, the major whitefly pests in vegetable crops. The main symptoms were severe yellowing on lower leaves, and curling on upper leaves of plant. Total DNA was extracted from tomato leaves using CTAB methods, while total RNA was extracted using NucleoSpin RNA Plant extraction kit (Macherey-Nagel). Because of occurring mixed symptom on an individual plant, hereby it is important to detect the causal agent to manage of the disease. Samples from symptomatic plants were analyzed by polymerase chain reaction (PCR) and shown to be infected with Tomato infectious chlorosis virus (TICV) (family Closteroviridae, genus Crinivirus) and a virus species belongs to the genus Begomovirus, family Geminiviridae. The research result is the first report of Crinivirus and Begomovirus double infection in single tomato fields in Indonesia. INTISARIPenyakit kuning pada tanaman tomat (Lycopersicon esculentum) telah ditemukan sejak tahun 2006 di Jawa Tengah, Indonesia. Epidemi penyakit tersebut terutama berkaitan dengan keberadaan dua spesies whitefly (Trialeurodes vaporariorum dan Bemisia tabaci). Gejala utama yang ditemukan adalah daun-daun pada tanaman bagian bawah berwarna kuning sedangkan daun daun pada tanaman bagian atas menunjukkan gejala keriting. Adanya gejala campuran pada satu individu tanaman maka perlu dideteksi penyebabnya untuk pengelolaannya. DNA total diekstraksi dari daun tomat yang terinfeksi menggunakan metode CTAB, sedangkan total RNA diekstraksi dengan menggunaan NucleoSpin RNA Plant extraction kit (Macherey-Nagel). Analisis sampel tanaman sakit menggunakan teknik poymerase chain reaction (PCR) menunjukkan adanya infeksi Tomato infectious chlorosis virus (TICV) (famili Closteroviridae, genus Crinivirus) dan satu spesies virus anggota genus Begomovirus, famili Geminiviridae. Hasil penelitian ini merupakan laporan pertama kali adanya infeksi ganda kelompok Crinivirus dan Begomovirus pada satu individu tanaman tomat di Indonesia.